Weight gain during pregnancy and low birth weight babies: a retrospective cohort study in Gianyar District, Bali - Putu Riza Kurnia Indriana; Luh Putu Suariyani; Ni Ketut Sutiari (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Low birth weight (LBW) is a major causal factor for neonatal and perinatal mortality. The aim of this study is to determine the risk of LBW incidence in pregnant women with weight gain not in accordance with the Institute of Medicine (IOM) standards. Methods: This study used a retrospective cohort design with data obtained from three Public Health Centres (PHCs) in Gianyar District over the period of January-December 2017. Samples in this study were 186 pregnant women with the following criteria: complete data on the mother’s medical record, had an antenatal care visit in the first trimester and at the end of the third trimester, at term delivery, not giving birth to twins and no complications during pregnancy. The sample size was determined with 95% confidence level, 80% power, the proportion of LBW in the group of inadequate weight gain of 26%, the proportion of LBW in the group of adequate weight gain of 9% and a relative risk (RR) estimate of 3.0. Data extracted from medical record consisted of weight gain, pre-pregnancy weight, height, upper arm circumference, hemoglobin level, employment, age, parity and birth weight. The cumulative incidence of LBW was calculated to determine the RR. Multivariate analysis with binary logistic regression was conducted to determine the adjusted RR (ARR). Results: The incidence of LBW in the group whose weight gain during pregnancy not in accordance with IOM standards was 59%, while those in accordance with the standards were 8.2% with RR=7.22 (95%CI: 3.96–13.19). The ARR for those with weight gain during pregnancy not in accordance with IOM standards was 15.33 (95%CI: 5.82-40.38). The incidence of LBW in the anemia group was 49% and not anemia group was 10%. The RR and ARR values for LBW in the anemia group were 4.72 (95%CI: 2.66-8.36) and 6.66 (95%CI: 2.53-17.53) respectively. Conclusion: Mothers experiencing weight gain during pregnancy that was not in accordance with IOM standards and anemia were found to increase the risk of LBW. Monitoring of weight gain during pregnancy should be implemented using the IOM standards and anemia prevention among pregnant mothers should be enhanced.